Effects of inland salt marsh wetland degradation on plant community characteristics and soil properties - Daiji Wan; Peng Yu; Lingyang Kong; Jinsong Zhang; Yanhui Chen; Dandan Zhao; Jiping Liu (Ecological Indicators, 2024)
Plant community characteristics and soil properties are critical indicators for evaluating wetland degradation and restoration. In order to investigate how the degradation of inland salt marsh wetlands affects plants and soils as well as the response relationship between plants and soils under different degradation degrees, this paper selected inland salt marsh wetlands with different degradation degrees in the wetland area of western Songnen Plain, and analyzed the characteristics of plant communities, soils and their relationships. The results show that: that the important value of Gramineae plants decreased by about 21% with increasing degradation, while the vital value of Cyperaceae and weeds increased by 10% and 9%, respectively. Plant height decreased significantly, and coverage and density showed a decreasing and then increasing trend. Overall, species diversity shows a trend of increasing and then decreasing, indicating that the structure of plant communities tends to be more straightforward and more complex with increasing degradation. Soil electrical conductivity, total organic carbon (TOC) and total nitrogen (TN) content decreased significantly with the degree of degradation from ND (non degradation) to HD (heavy degradation) by 34.08%, 19.56%, and 35.82%, respectively. Soil C:N increased from 13.13 to 17.97. Soil N:P and C:P decreased from 5.56 to 3.28 and from 71.59 to 54.02, respectively. Soil factors affecting wetland plants were inconsistent at different stages of degradation. Changes in soil nitrogen and phosphorus content were correlated with changes in wetland vegetation community structure. Therefore, exploring how wetland degradation affects plants and soils can provide a scientific basis for wetland degradation assessment and wetland restoration.